(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Most leukoplakia patches are not cancer. But some patches show early signs of cancer. Cancers in the mouth can occur next to areas of leukoplakia. White areas mixed with red areas, also called speckled leukoplakia, may possibly lead to cancer. It’s best to see your dentist or doctor if you have any changes in your mouth that do not go away.